Steel sheet for gas soft nitriding
Patent Information
- Application Number
- JP2023500944
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-02-18
- Filing Date
- 2022-02-18
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2042-02-18
AI Technical Summary
【0012】 本発明の上記態様によれば、一般に求められる引張強さ、伸び、曲げ特性を有することを前提として、表面硬化処理としてガス軟窒化処理を行った場合に形状変化量を低減させることのできる、ガス軟窒化用鋼板を提供することができる。
Smart Images

Figure 0007633558000005 
Figure 0007633558000006 
Figure 0007633558000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel plate for gas soft nitriding. This application claims priority based on Japanese Patent Application No. 2021-024185, filed on February 18, 2021, the contents of which are incorporated herein by reference. [Background technology]
[0002] Parts that transmit power around the engine are repeatedly subjected to contact, friction, and load between parts. Therefore, extremely high durability and wear resistance are required. To achieve this performance, these parts are often subjected to surface hardening treatments such as carburizing and quenching and nitriding. Among these parts, gas soft nitriding is applied to the surface hardening of thin steel plate parts. This gas soft nitriding is performed at high temperatures in an atmosphere containing carbon as well as nitrogen, for example, so that the diffusion rate of nitrogen is high and a specified hardness characteristic can be obtained in a short treatment time. In addition, since the treatment temperature is in a temperature range where steel materials do not undergo austenite transformation (generally 500°C or higher and Ac3 temperature or lower), the change in part dimensions or shape due to this treatment (hereinafter sometimes simply referred to as shape change) is smaller than other carburizing and quenching treatments. If the shape change due to this surface hardening treatment is small, the shape precision of the part can be easily improved.
[0003] The geometric accuracy of parts is an important requirement for assembly, but it is also a characteristic that strongly affects the durability and wear resistance of parts, because even slight geometric distortion increases the contact area or contact pressure between parts when they are in use. This shape change during the surface hardening process occurs not only during the final cooling of the surface hardening process, but also during the heating process until the above-mentioned processing temperature is reached. The shape change of the part during heating and cooling is caused by thermal expansion and contraction, as well as by the release of residual stress introduced in the blank trimming and pressing processes that precede the surface hardening process during heating. As such, the changes in size and shape caused by the surface hardening process are affected not only by the processing conditions of the surface hardening process, but also by the conditions of the blank trimming and pressing processes that precede the surface hardening process, so it is not clear how to minimize them.
[0004] As described above, gas soft nitriding treatment causes less shape change than other surface hardening treatments. However, since shape change occurs due to various factors, even when gas soft nitriding treatment is performed, a certain amount of shape change may occur. In addition, when such shape change is expected to occur and the likelihood of shape change can be predicted, the press shape (press die shape) can be modified in advance to a shape different from that of the final product, taking into account the likelihood of the shape change. However, in the current situation, when an (unpredictable) shape change occurs due to surface hardening treatment, only a posteriori measures (for example, shape correction or disposal of products that are not easy to correct) can be taken, such as performing shape correction after surface hardening treatment. In other words, even in gas soft nitriding treatment, which is generally said to cause little shape change, it is a fact that economic losses are generated in industrial production due to shape change caused by surface hardening treatment.
[0005] Regarding steel sheets for gas soft nitriding, for example, Patent Document 1 describes a method for producing a steel sheet having a composition, by mass%, of C: more than 0.01% and 0.09% or less, Si: 0.005 to 0.5%, Mn: 0.01 to 3.0%, Al: 0.005 to 2.0%, Cr: 0.50 to 4.0%, P: 0.10% or less, S: 0.01% or less, and N: 0.010% or less, with the balance being Fe and unavoidable impurities, which is hot-rolled at a finishing temperature of 870°C or more, pickled, cold-rolled, and then recrystallized and annealed at a temperature of 800 to 950°C, thereby achieving a grain boundary area per unit volume Sv of 80 mm -1 Above 1300mm -1A method for producing a cold rolled steel sheet for nitriding treatment is disclosed, which is characterized by controlling the following: Patent Document 2 also describes a steel sheet having a chemical composition, in mass%, of C: 0.02% or more and less than 0.07%, Si: 0.10% or less, Mn: 1.1 to 1.8%, P: 0.05% or less, S: 0.01% or less, Al: 0.10 to 0.45%, N: 0.01% or less, Ti: 0.01 to 0.10%, Nb: 0 to 0.1%, Mo: 0 to 0.1%, V: 0 to 0.1%, Cr: 0 to 0.2%, and the balance: Fe and impurities, which satisfies Mn+Al≧1.5, the total content of Ti, Nb, Mo, V, and Cr present as precipitates in the steel sheet is less than 0.03% in mass%, the area ratio of ferrite is 80% or more, and the dislocation density of ferrite at a position 50 μm from the steel sheet surface is 1×10 14 ~1×10 16 m -2 The present invention discloses a steel sheet for soft nitriding treatment having a metal structure of [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent No. 4462264 [Patent Document 2] International Publication No. 2015 / 190618 Summary of the Invention [Problem to be solved by the invention]
[0007] The objective of Patent Document 1 is to propose an advantageous manufacturing method for a cold-rolled steel sheet for nitriding, which can obtain sufficient surface hardening ability and hardening depth by nitriding. Also, Patent Document 2 aims to improve fatigue properties that are insufficient in the conventional technology without reducing productivity and cost, and the objective of Patent Document 2 is to provide a soft-nitrided steel that has excellent workability before soft-nitriding and has high fatigue properties by applying soft-nitriding. That is, neither Patent Document 1 nor Patent Document 2 takes into consideration the suppression of shape change due to surface hardening treatment.
[0008] As described above, conventionally, no technology has been proposed for suppressing shape changes during surface hardening treatment such as gas soft nitriding by controlling the chemical composition or structure of a steel sheet. An object of the present invention is to provide a steel plate for gas soft-nitriding, which can reduce the amount of shape change when gas soft-nitriding is performed as a surface hardening treatment. [Means for solving the problem]
[0009] As mentioned above, the change in dimensions and shape due to the surface hardening treatment is affected not only by the treatment conditions of the surface hardening treatment, but also by the conditions of the preceding blank trim (hereinafter also referred to as "trim") and pressing processes, so it is not clear how to minimize it. In order to solve the problem, the inventors first thought that it would be effective to clarify and improve the factors that cause shape changes in each of the trim / press process and the surface hardening treatment. In the trim and press process, it is considered effective to review the intermediate shape and adjust the blank holding force to introduce plastic strain by tension, etc., to reduce residual stress in each intermediate forming process until the final shape is obtained, and to improve the positioning accuracy of the intermediate formed product in the next process by using press technology. In the latter surface hardening process, it is considered effective to increase the uniformity of the temperature in the treatment furnace and strictly control the cooling rate in the final cooling process. However, such improvements are based on the premise that the material used for pressing and surface hardening always behaves in the same way, and in reality, it is considered that shape changes will occur even if the above conditions are uniform.
[0010] The present inventors have investigated the shape changes before and after gas soft nitriding for various steel sheets. As a result, they have newly discovered that the difference in effective grain size in the width direction (sheet width direction) is the cause of the shape changes in steel sheets having a specified chemical composition and metal structure. They have also discovered that in order to reduce this difference in effective grain size and suppress the shape changes due to gas soft nitriding, it is effective to control the conditions such as the heating conditions before hot rolling and the hot rolling conditions.
[0011] The present invention has been made based on the above findings. The gist of the present invention is as follows. [1] A steel plate for gas soft nitriding according to one embodiment of the present invention has a chemical composition, in mass%, of C: 0.02 to 0.10%, Si: 0.001 to 0.100%, Mn: 0.70 to 1.65%, P: 0.060% or less, S: 0.005% or less, sol.Al: 0.020 to 0.450%, Ti: 0.020 to 0.120%, Cr: 0.100 to 0.450%, N: 0.0003 to 0.0070%, Cu: 0 to 0.40%, Ni: 0 to 0.30%, Nb: 0 to 0.080%, V: 0 to 0.080%, Mo: 0 to 0.0 0.100%, B: 0-0.0020%, Ca: 0-0.0100%, REM: 0-0.0100%, Sn: 0-0.0300%, Sb: 0-0.0100%, As: 0-0.0100%, Mg: 0-0.0300%, and the balance: Fe and impurities, and the following formulas (1) and (2) are satisfied, and the metal structure is, in area %, ferrite: 30.0-100.0%, martensite: 0-5.0%, bainite: 0-70.0%, retained austenite: 0-3.0%, pearlite: 0-3.0%, Consists of When the plate thickness is t and the plate width, which is the width in the direction perpendicular to the rolling direction, is w, and the effective grain size is measured at seven positions, namely, a depth position of t / 4 from the surface and positions of w / 8, w / 4, 3w / 8, w / 2, 5w / 8, 3w / 4, and 7w / 8 in the width direction from the end in the width direction, the average effective grain size, which is the average of the effective grain sizes at the seven positions, is 8.0 to 35.0 μm, and the effective grain size difference, which is the difference between the maximum value and the minimum value of the effective grain sizes at the seven positions, is 10.0 μm or less. [sol.Al]+[Cr]≦0.482····Formula (1) 94<64×[Mn]+156×[Cr]+190×[sol.Al]-9×[Mn] 2 -86×[Cr] 2 -328×[sol.Al] 2 ...Equation (2) Here, the [element symbol] indicates the content by mass % of the element represented by the element symbol. [2] The steel plate for gas soft nitriding described in [1] may contain, in mass%, one or more elements selected from the group consisting of Cu: 0.01 to 0.40%, Ni: 0.01 to 0.30%, Nb: 0.001 to 0.080%, V: 0.001 to 0.080%, Mo: 0.001 to 0.100%, B: 0.0001 to 0.0020%, Ca: 0.0001 to 0.0100%, REM: 0.0001 to 0.0100%, Sn: 0.0001 to 0.0300%, Sb: 0.0001 to 0.0100%, As: 0.0001 to 0.0100%, and Mg: 0.0001 to 0.0300%. [3] The steel plate for gas soft nitriding according to [1] or [2] may have a tensile strength of 370 MPa or more and an elongation of 13.0% or more as measured by a No. 5 test piece of JIS Z2241:2011. Effect of the Invention
[0012] According to the above-mentioned aspect of the present invention, a steel plate for gas soft nitriding can be provided that has the generally required tensile strength, elongation, and bending properties, and that can reduce the amount of shape change when subjected to gas soft nitriding treatment as a surface hardening treatment. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a diagram showing the shape of a test piece for a shape change investigation test. [Diagram 2] FIG. 2 is a diagram showing the observation positions of the metal structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, a gas soft-nitriding steel plate according to one embodiment of the present invention (hereinafter, referred to as the gas soft-nitriding steel plate according to this embodiment) and its manufacturing method, as well as a gas soft-nitriding part obtained from the gas soft-nitriding steel plate according to this embodiment (the gas soft-nitriding part according to this embodiment) will be described in detail. However, the present invention is not limited to only the configuration disclosed in this embodiment, and various modifications are possible within the scope of the present invention.
[0015] <Steel plate for gas nitrocarburizing> The steel plate for gas soft nitriding according to this embodiment has a predetermined chemical composition, and the metal structure contains, in area %, ferrite: 30.0 to 100.0%, martensite: 0 to 5.0%, bainite: 0 to 70.0%, retained austenite: 0 to 3.0%, and pearlite: 0 to 3.0%. When the plate thickness is t and the plate width, which is the width in the direction perpendicular to the rolling direction, is w, and the effective grain size is measured at seven positions, namely, a position of t / 4 in the plate thickness direction from the surface (a depth position of t / 4 from the surface) and positions of w / 8, w / 4, 3w / 8, w / 2, 5w / 8, 3w / 4, and 7w / 8 in the width direction from the end in the width direction, the average effective grain size, which is the average of the effective grain sizes at the seven positions, is 8.0 to 35.0 μm, and the effective grain size difference, which is the difference between the maximum value and the minimum value of the effective grain sizes at the seven positions, is 10.0 μm or less. The reasons for each limitation will be explained below.
[0016] (chemical composition) First, the chemical composition of the steel plate for gas soft nitriding according to this embodiment will be described. In the following, the numerical ranges described with "~" include both the lower and upper limit values. However, the numerical values indicated as "less than" and "more than" do not include the numerical range. All "%" in the chemical composition refers to "mass %" unless otherwise specified.
[0017] C: 0.02 to 0.10% C is an element that affects the strength of a steel sheet. If the C content is less than 0.02%, the strength generally required for a steel sheet for gas soft nitriding cannot be sufficiently ensured. Therefore, the C content is set to 0.02% or more. The C content is preferably 0.03% or more, and more preferably 0.04% or more or 0.05% or more. On the other hand, if the C content exceeds 0.10%, the elongation decreases. Therefore, the C content is set to 0.10% or less. The C content is preferably 0.08% or less, more preferably 0.07% or less or 0.06% or less.
[0018] Silicon: 0.001 to 0.100% Silicon is an element that forms a scale pattern on the steel sheet surface. In order to remove the scale pattern, pickling is generally performed, but if the Si content exceeds 0.100%, the pickling cost becomes significantly high. Therefore, the Si content is set to 0.100% or less. The Si content is preferably 0.085% or less or 0.070% or less, and more preferably 0.055% or less or 0.040% or less. On the other hand, in order to reduce the cost of pickling, the lower the Si content, the more preferable, but if the Si content is less than 0.001%, the raw material cost will be high. Therefore, the Si content is set to 0.001% or more. The Si content is preferably 0.003% or more or 0.005% or more, more preferably 0.008% or more or 0.015% or more.
[0019] Mn: 0.70-1.65% Mn is an element that, when contained in combination with Cr and Al, increases the density of nitrides after gas soft-nitriding, thereby improving the wear resistance of the steel plate (including gas soft-nitrided parts, the same applies below) after gas soft-nitriding. If the Mn content is less than 0.70%, nitrides with sufficient density cannot be obtained after gas soft-nitriding. Therefore, the Mn content is set to 0.70% or more while satisfying the formula (2) described later. The Mn content is preferably 0.80% or more or 0.85% or more, and more preferably 0.90% or more or 1.00% or more. On the other hand, if the Mn content exceeds 1.65%, the area ratio of ferrite in the metal structure decreases, and elongation decreases. Therefore, the Mn content is set to 1.65% or less. The Mn content is preferably 1.60% or less or 1.50% or less, and more preferably 1.40% or less or 1.30% or less.
[0020] P:0.060% or less P is an element (impurity) that is mixed in during the manufacturing process of the steel plate for gas soft nitriding. If the P content is high, the grain boundaries become embrittled, making it easier for cracks to occur during the manufacturing of the steel plate for gas soft nitriding. Therefore, the P content is set to 0.060% or less. The P content is preferably 0.040% or less or 0.030% or less, and more preferably 0.020% or less or 0.015% or less. The lower the P content, the more preferable it is, and it may be 0%, but it may be 0.001% or more or 0.003% or more in consideration of the dephosphorization cost.
[0021] S: 0.005% or less S is an element (impurity) that is mixed in during the manufacturing process of a steel plate for gas soft nitriding. If the S content is high, MnS is formed, which makes it easier for cracks to occur during press forming. Therefore, the S content is set to 0.005% or less. The S content is preferably 0.004% or less, and more preferably 0.003% or less. The lower the S content, the more preferable it is, and it may be 0%, but it may be 0.001% or more or 0.002% or more in consideration of the desulfurization cost.
[0022] Sol.Al: 0.020~0.450% Al is an element that, when contained in combination with Cr and Mn, has the effect of increasing the density of nitrides after gas soft-nitriding and improving the wear resistance of a steel sheet after gas soft-nitriding. If the sol.Al (acid-soluble Al) content is less than 0.020%, it becomes impossible to prevent the coarsening of the austenite grain size during slab heating, and as a result, there is a risk that the variation in the effective grain size in the width direction of the steel sheet will increase. Therefore, the sol.Al content is set to 0.020% or more while satisfying the formulas (1) and (2) described below. The sol.Al content is preferably 0.030% or more, 0.040% or more, 0.060% or more, or 0.090% or more, and more preferably 0.200% or more. On the other hand, if the sol.Al content exceeds 0.450%, nozzle clogging during continuous casting becomes more likely to occur, resulting in reduced productivity. Therefore, the sol.Al content is set to 0.450% or less. The sol.Al content is preferably 0.400% or less or 0.300% or less, and more preferably 0.200% or less or 0.150% or less.
[0023] Ti: 0.020~0.120% Ti is an element that forms Ti carbide and contributes to improving the strength of the steel sheet, and also has the effect of making the effective grain size fine by making the austenite grain size fine in the hot rolling process. If the Ti content is less than 0.020%, the effective grain size cannot be sufficiently fine. Therefore, the Ti content is set to 0.020% or more. The Ti content is preferably 0.025% or more or 0.035% or more, and more preferably 0.045% or more or 0.055% or more. On the other hand, if the Ti content exceeds 0.120%, the elongation decreases. Therefore, the Ti content is set to 0.120% or less. The Ti content is preferably 0.110% or less or 0.100% or less, and more preferably 0.080% or less or 0.070% or less.
[0024] Cr: 0.100~0.450% Cr is an element that, when contained in combination with Mn and Al, has the effect of increasing the density of nitrides after gas soft-nitriding and improving the wear resistance of the steel sheet after gas soft-nitriding. If the Cr content is less than 0.100%, nitrides with sufficient density cannot be obtained after gas soft-nitriding. Therefore, the Cr content is set to 0.100% or more while satisfying the formulas (1) and (2) described below. The Cr content is preferably 0.120% or more or 0.140% or more, and more preferably 0.160% or more or 0.190% or more. On the other hand, if the Cr content exceeds 0.450%, the density of the nitrides after gas soft nitriding becomes excessively high. Therefore, the Cr content is set to 0.450% or less. The Cr content is preferably 0.400% or less, 0.350% or less, or 0.300% or less, and more preferably 0.250% or less, or 0.220% or less.
[0025] N: 0.0003~0.0070% N is an element that forms coarse nitrides and causes embrittlement cracking in slabs. Therefore, the N content is set to 0.0070% or less. The N content is preferably 0.0050% or less or 0.0040% or less. On the other hand, the lower the N content, the better, but N is an element that is mixed in during the manufacturing process of the steel plate for gas soft nitriding, and if the N content is less than 0.0003%, the cost will increase significantly. Therefore, the N content is set to 0.0003% or more. The N content is preferably 0.0005% or more or 0.0010% or more.
[0026] Equation (1) and Equation (2) Of the above components, the sol.Al content and the Cr content are within the ranges of formula (1) and formula (2), and the Mn content is limited to the range of formula (2). When the left side of formula (1) exceeds 0.482, the effective hardening depth, which is the depth (distance from the surface) of a region in a steel plate (including a part) after gas soft-nitriding treatment where the hardness is 50 Hv or more higher than the hardness of the parent phase (a portion not hardened by gas soft-nitriding treatment, for example, the hardness at the position of tc / 4 when the thickness is tc), becomes less than 0.300 mm. Furthermore, when the right-hand side of formula (2) is 94 or less, the surface hardness of the steel plate after gas soft-nitriding treatment does not reach 500 Hv or more, which is the surface hardness generally required for gas soft-nitrided parts. Therefore, the sol. Al content, the Cr content, and the Mn content are set within the above-mentioned ranges so as to satisfy the formulas (1) and (2). [sol.Al]+[Cr]≦0.482····Formula (1) 94<64×[Mn]+156×[Cr]+190×[sol.Al]-9×[Mn] 2 -86×[Cr]2 -328×[sol.Al] 2 ...Equation (2) Here, [element symbol] is the content in mass% of the element represented by that element symbol in the steel. If necessary, the right side of formula (1) may be 0.478, 0.472, 0.467, 0.460, or 0.440 instead of 0.482. The lower limit of "[sol.Al] + [Cr]" in formula (1) is 0.120, but may be 0.150, 0.180, or 0.200. In addition, the left side of formula (2) may be 97, 100, or 105 instead of 94.
[0027] The gas nitrocarburizing steel plate according to this embodiment basically contains the above elements in its chemical composition, with the remainder being Fe and impurities. Here, the impurities refer to components that are mixed in due to various factors in the raw materials such as ores and scraps and the manufacturing process when manufacturing the steel plate, and are permissible within a range that does not adversely affect the present invention. On the other hand, in order to improve various properties, Cu, Ni, Nb, V, Mo, B, Ca, REM, Sn, Sb, As, and Mg may be further contained within the range described below. However, since the inclusion of these elements is not essential, the lower limit is 0% for each of them. These elements may be contained as impurities as long as they are within the content range described below.
[0028] Cu: 0-0.40% Cu is an element that contributes to improving the surface hardness after gas soft nitriding. Therefore, Cu may be contained. To obtain the above effects, the Cu content is preferably 0.01% or more, and more preferably 0.03% or 0.07% or more. On the other hand, if the Cu content exceeds 0.40%, hot cracking during manufacturing is likely to occur. Therefore, if Cu is contained, the Cu content is set to 0.40% or less. The Cu content is preferably 0.35% or less or 0.35% or less, and more preferably 0.25% or less or 0.20% or less.
[0029] Ni: 0 to 0.30% Ni is an element that contributes to improving the surface hardness after gas soft nitriding. Ni is also an element that has the effect of suppressing hot cracking when Cu is contained. Therefore, when Cu is contained, Ni is preferably contained. To obtain the above effect, the Ni content is preferably 0.01% or more, and more preferably 0.03% or more. On the other hand, if the Ni content is excessive, the alloy cost increases and the economy is impaired. Therefore, when Ni is contained, the Ni content is set to 0.30% or less. The Ni content is preferably 0.25% or less or 0.20% or less, and more preferably 0.15% or less or 0.10% or less.
[0030] Nb: 0 to 0.080% Nb is an element that has the effect of refining the austenite grain size during hot rolling, and through this effect, has the effect of reducing the average effective crystal grain size of the steel sheet. Therefore, Nb may be contained. To obtain the above effect, the Nb content is preferably 0.001% or more, and more preferably 0.005% or more or 0.010% or more. On the other hand, if the Nb content exceeds 0.080%, the toughness of the slab after casting decreases, which causes cracking of the slab. Therefore, if Nb is contained, the Nb content is set to 0.080% or less. The Nb content is preferably 0.070% or less or 0.0.060% or less, and more preferably 0.050% or less or 0.040% or less.
[0031] V: 0~0.080% V is a nitride-forming element and has the effect of improving the surface hardness after soft nitriding. Therefore, V may be contained. To obtain the above effect, the V content is preferably 0.001% or more, and more preferably 0.003% or more or 0.010% or more. On the other hand, if the V content exceeds 0.080%, the slab toughness decreases, and many slab cracks occur before charging into the heating furnace, making production difficult. Therefore, if V is contained, the V content is set to 0.080% or less. The V content is preferably 0.070% or less or 0.050% or less, and more preferably 0.040% or less or 0.030% or less.
[0032] Mо:0~0.100% Mo is a nitride-forming element and has the effect of improving the surface hardness. Therefore, Mo may be contained. To obtain the above effect, the Mo content is preferably 0.001% or more, and more preferably 0.003% or more or 0.005% or more. On the other hand, if the Mo content exceeds 0.100%, the hardenability increases, the area ratio of martensite increases, and the specified metal structure cannot be obtained in the steel sheet. Therefore, when Mo is contained, the Mo content is set to 0.100% or less. The Mo content is preferably 0.080% or less or 0.060% or less, and more preferably 0.040% or less or 0.030% or less.
[0033] B: 0~0.0020% B is a nitride-forming element and has the effect of improving the surface layer hardness. Therefore, B may be contained. To obtain the above effect, the B content is preferably 0.0001% or more, and more preferably 0.0003% or more or 0.0006% or more. On the other hand, if the B content exceeds 0.0020%, the hardenability increases, the area ratio of martensite increases, and the specified metal structure cannot be obtained in the steel sheet. Therefore, if B is contained, the B content is set to 0.0020% or less. The B content is preferably 0.015% or less or 0.0010% or less, and more preferably 0.0008% or less or 0.0004% or less.
[0034] Ca: 0 to 0.0100% Ca is an element that forms fine sulfides and has the effect of improving press formability. Therefore, Ca may be contained. In order to obtain the above effect, the Ca content is preferably 0.0001% or more, and more preferably 0.0005% or more or 0.0010% or more. On the other hand, if the Ca content exceeds 0.0100%, it may accumulate as an oxide in the casting nozzle during casting, causing clogging of the nozzle. Therefore, if Ca is contained, the Ca content is set to 0.0100% or less. The Ca content is preferably 0.0080% or less or 0.0060% or less, and more preferably 0.0040% or less or 0.0020% or less.
[0035] REM: 0~0.0100% Rare earth elements (i.e., REMs) such as Sc, Y, La, Lu, and Ce have the effect of reducing the effective grain size difference by delaying the growth of γ grains to a certain degree or more during rolling. Therefore, they may be contained. To obtain the above effect, the REM content is preferably 0.0001% or more, and more preferably 0.0005% or more or 0.0010% or more. On the other hand, if the total REM content exceeds 0.0100%, the effect is saturated and the cost of adding them leads to a decrease in economic efficiency. Therefore, if REM is added, the REM content is set to 0.0100% or less. The REM content is preferably 0.0080% or less or 0.0060% or less, and more preferably 0.0040% or less or 0.0020% or less.
[0036] Sn: 0 to 0.0300% Sn is an element effective in improving corrosion resistance, and therefore may be contained. In order to obtain the above effects, the Sn content is preferably 0.0001% or more, and more preferably 0.0010% or more. On the other hand, if the Sn content exceeds 0.0300%, surface cracks occur during rolling, significantly reducing productivity. Therefore, the Sn content is set to 0.0300% or less. The Sn content is preferably 0.0250% or less or 0.0200% or less, and more preferably 0.0150% or less or 0.0100% or less.
[0037] Sb: 0 to 0.0100% Sb is an element that is effective in improving corrosion resistance, and therefore may be contained. In order to obtain the above effects, the Sb content is preferably 0.0001% or more, and more preferably 0.0010% or more. On the other hand, if the Sb content exceeds 0.0100%, surface cracks occur during rolling, significantly reducing productivity. Therefore, the Sb content is set to 0.0100% or less. The Sn content is preferably 0.0080% or less or 0.0060% or less, more preferably 0.0040% or less or 0.0020% or less.
[0038] As: 0~0.0100% As is an element effective in improving the machinability of steel, and therefore may be contained. In order to obtain the above effect, the As content is preferably 0.0001% or more, and more preferably 0.0010% or more. On the other hand, if the As content exceeds 0.0100%, surface cracks occur during rolling, significantly reducing productivity. Therefore, the As content is set to 0.0100% or less. The As content is preferably 0.0080% or less or 0.0060% or less, and more preferably 0.0040% or less or 0.0020% or less.
[0039] Magnesium: 0 to 0.0300% Mg is an element that has the effect of suppressing the deterioration of bendability due to coarse nitrides by becoming a generation site of nitrides formed after solidification. Therefore, Mg may be contained. To obtain the above effect, the Mg content is preferably 0.0001% or more, and more preferably 0.0005% or more or 0.0010% or more. On the other hand, if the Mg content exceeds 0.0300%, sparks will occur when the raw materials are added, significantly impairing productivity. Therefore, if Mg is contained, the Mg content is set to 0.0300% or less. The Mg content is preferably 0.0250% or less or 0.0200% or less, and more preferably 0.0100% or less or 0.0050% or less.
[0040] The above-mentioned chemical compositions may be measured by a general analytical method. For example, they may be measured using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). C and S may be measured using a combustion-infrared absorption method, and N may be measured using an inert gas fusion-thermal conductivity method.
[0041] (Metal structure (microstructure)) Next, the reasons for limiting the metal structure will be described. In the following, % in the metal structure means area %.
[0042] (Ferrite: 30.0 to 100.0%) In the steel plate for gas soft nitriding according to this embodiment, the area ratio of ferrite in the metal structure is set to 30.0% or more in order to ensure sufficient elongation. The area ratio of ferrite is preferably 35.0% or more or 40.0% or more, more preferably 50.0% or more, 60.0% or more, or 70.0% or more. The upper limit of the area ratio of ferrite is 100%. The area ratio of ferrite may be 95.0% or less, 90.0%, 80.0% or less, or 75.0% or less, as necessary.
[0043] (Martensite: 0~5.0%) Martensite is an effective structure for improving the strength of a steel sheet, but if the area ratio of martensite exceeds 5.0%, the bendability of the steel sheet decreases. Therefore, the area ratio of martensite in the metal structure is set to 5.0% or less. The area ratio of martensite may be 4.5% or less, 4.0% or less, 3.5% or less, or 3.0% or less as necessary. Since martensite does not necessarily need to be contained, the area ratio may be 0%. The area ratio of martensite may be 0.5% or more, 1.0% or more, 1.5% or more, or 2.0% or more as necessary. The martensite may be as quenched (so-called fresh martensite), or may be martensite that has been tempered (including self-tempering) at 370°C or less (so-called tempered martensite).
[0044] (Bainite: 0~70.0%) Bainite is an effective structure for increasing strength without reducing bendability, and may be contained. To obtain this effect, the bainite area ratio is preferably 10.0% or more. The bainite area ratio may be 15.0% or more, 20.0% or more, 25.0% or more, 30.0% or more, or 35.0% or more, as necessary. On the other hand, if the area ratio of bainite exceeds 70.0%, ferrite of 30.0% or more cannot be secured, and sufficient elongation cannot be obtained. Therefore, the area ratio of bainite in the metal structure is set to 70.0% or less. The area ratio of bainite may be set to 65.0% or less, 60.0% or less, 55.0% or less, 50.0% or less, or 45.0% or less, as necessary. Since it is not necessary to include bainite, the area ratio may be 0%.
[0045] (Other organizations) In the steel plate for gas soft nitriding according to this embodiment, the remainder other than ferrite, martensite, and bainite is not limited, but may contain, for example, pearlite and / or retained austenite. The area ratio of the retained austenite is 3.0% or less, and preferably 2.0% or less or 1.0% or less. The area ratio of the pearlite is 3.0% or less, and preferably 2.0% or less or 1.0% or less. The area ratios of the retained austenite and the pearlite may each be 0%. The sum of the area ratios of the retained austenite and the pearlite may be 3.0% or less, 2.0% or less, or 1.0% or less.
[0046] (effective grain size) In the steel plate for gas soft nitriding according to this embodiment, when the effective grain size is measured at seven positions, namely, a position at t / 4 in the thickness direction from the surface and a position at w / 8, w / 4, 3w / 8, w / 2, 5w / 8, 3w / 4, and 7w / 8 in the width direction (on a straight line perpendicular to the rolling direction) from the end in the width direction (direction perpendicular to the rolling direction), where t is the thickness of the steel plate and w is the width perpendicular to the rolling direction, the average effective grain size, which is the average of the effective grain sizes at the seven positions, is 8.0 to 35.0 μm, and the effective grain size difference, which is the difference between the maximum and minimum values of the effective grain sizes at the seven positions, is 10.0 μm or less. As described above, in gas soft-nitriding parts, the change in shape due to the gas soft-nitriding treatment becomes an issue. The present inventors investigated gas soft-nitriding test pieces of hat-formed materials described below, and conducted studies to minimize the change in shape due to the gas soft-nitriding treatment and maximize the performance of the parts. Specifically, 10 mm-wide ring-shaped test pieces were created by shear trimming (punching using a trim die) at the 1 / 2, 1 / 4, and 1 / 8 positions in the width direction of the steel plate, as shown in Figure 1. Large residual stress usually remains at the trimmed edges. In order to investigate the effects of this, the inner and outer circumferences of the ring test pieces were left as shear trimmed edges. Gas nitrocarburizing treatment was carried out on this ring-shaped test piece in an atmosphere of a mixed gas with a volume ratio of 45% nitrogen, 50% ammonia, and 5% carbon dioxide. The treatment temperature was 570°C, and the soaking time was 1 hour. After treatment in this atmosphere, temperature, and time, the ring-shaped gas nitrocarburizing test piece was cooled to room temperature by air cooling, and the shape change was measured. The shape change was measured by measuring the outer diameter in the rolling direction, the direction perpendicular to the rolling direction, and the directions at 45° and 135° to the rolling direction before and after treatment. Those with changes in each direction exceeding 0.5% (1 mm in this test) were deemed to have poor dimensional accuracy and would create the above-mentioned problems as parts, and were therefore rejected. As a result of the investigation, it was found that in order to improve the dimensional accuracy, it is effective to set the difference between the maximum and minimum effective grain size at each position in the width direction of the steel plate (i.e., the effective grain size difference) to 10.0 μm or less. If the effective grain size difference exceeds 10.0 μm, the shape change after gas soft nitriding treatment becomes large. Although it is unclear why reducing the variation in effective crystal grain size in the width direction suppresses the change in shape after gas soft nitriding treatment, it is presumed that the homogenization of the metal structure in the width direction of the steel plate reduces the strain or residual stress inside the steel plate, and as a result, the change in shape after heating is suppressed. Regarding the variation in effective grain size in the width direction, it was found that the difference in effective grain size at eight equal positions across the width of the steel plate roughly represents the difference in effective grain size across the entire width direction. Therefore, in the steel plate for gas soft nitriding according to this embodiment, the effective grain size difference at seven positions from the end in the width direction to the positions of w / 8, w / 4, 3w / 8, w / 2, 5w / 8, 3w / 4, and 7w / 8 in the width direction is set to 10.0 μm or less. The effective grain size difference is preferably 9.0 μm or less, more preferably 8.0 μm or less or 7.0 μm or less. The effective grain size is less likely to vary in the rolling direction than in the width direction, so the effective grain size difference in the width direction should be set within a predetermined range. If the average effective grain size is less than 8.0 μm, the effective hardening depth is less than 0.300 mm. On the other hand, if the average grain size exceeds 35.0 μm, the bendability is reduced. Therefore, the average effective grain size is set to 8.0 to 35.0 μm. Furthermore, the "effective crystal grain size difference / average effective crystal grain size" may be 0.80 or less, 0.70 or less, 0.60 or less, 0.50 or less, or 0.40 or less.
[0047] Even if the material properties (hardness, etc.) in the width direction are small, it cannot be said that the difference in effective grain size is small. From the research conducted by the present inventors, even in steel sheets with small material properties in the width direction, the effective grain size always varies greatly in the width direction.
[0048] The area ratios of ferrite, martensite, bainite, pearlite, and austenite in the metal structure, as well as the average effective crystal grain size and the effective crystal grain size difference, can be determined by the following method.
[0049] (area ratio of ferrite) The area ratio of ferrite is obtained by performing EBSD analysis using an apparatus consisting of a thermal field emission scanning electron microscope (JEOL JSM-7001F) and an EBSD detector (TSL DVC5 type detector). Specifically, when the width of the steel plate for gas soft nitriding according to this embodiment is the width perpendicular to the rolling direction, samples are taken from the positions of w / 8, w / 4, 3w / 8, w / 2, 5w / 8, 3w / 4, and 7w / 8 in the width direction from the end in the width direction so that the size is 10 mm in the direction perpendicular to the rolling direction. Then, for each sample, the cross section perpendicular to the rolling direction is roughly polished with #1000, and mirror polished with a polishing solution in which diamond powder with a grain size of 1 to 3 μm is dispersed, and then the polishing strain on the surface is removed by electrolytic polishing to finish it into a sample for observation. For each of the obtained observation samples, when the thickness of the steel plate for gas soft nitriding according to this embodiment is t, the observation positions are set to a range of 200 μm in the plate thickness direction and 400 μm in the perpendicular direction, with the position of t / 4 (depth position of t / 4) in the plate thickness direction from the surface of the plate thickness direction cross section being approximately the center. That is, the observation positions are the positions shown in FIG. 2. The sample is subjected to EBSD (Electron Backscatter Diffraction) analysis to obtain crystal orientation information. During EBSD analysis, the vacuum level in the apparatus was 1.0×10 -4 The conditions are as follows: 1. the acceleration current is 15 kV, 2. the probe current level is 13 to 15, 3. the electron beam probe level is 62, 4. the WD is 15 mm, and the measurement interval is 0.05 μm to 0.5 μm. Using the crystal orientation information obtained by this EBSD analysis, the software "OIM Analysis (registered trademark)" attached to the EBSD analyzer is used to identify ferrite and calculate its area ratio. In this embodiment, the boundary where the orientation difference between adjacent measurement points is 15° or more from the figure determined to be a bcc phase on the inverse pole color map output by "OIM Analysis (registered trademark)" is defined as a grain boundary, and the GAM value is calculated for each crystal grain. Those with this GAM value of 0.5 or less are considered to be ferrite grains, and the area ratio of these ferrite grains is calculated. The area ratio of these ferrite grains is measured for the observation sample at each width direction position, and the average value is taken as the ferrite area ratio.
[0050] (area ratio of martensite) The area ratio of martensite is determined by using a metallographic photograph taken after the structure is revealed by using a LePeller etching solution, taking the structure observed as a white contrast as martensite, and measuring its area ratio. The sampling positions and observation positions of the observation samples are the same as those of the above-mentioned ferrite, and the average value of the area ratios of martensite obtained for each sample is taken as the area ratio of martensite of the steel plate for gas soft nitriding according to this embodiment.
[0051] (area ratio of pearlite) The area ratio of pearlite is determined using a metallographic photograph that is revealed by using a nital etching solution and photographed. Specifically, in the metallographic photograph, crystal grains containing lamellar carbides are defined as pearlite, and the area ratio is determined. The sampling positions and observation positions of the observation samples are the same as those of the ferrite samples, and the area ratio of pearlite is determined from each sample, and the average value of the pearlite area ratios of all samples is defined as the area ratio of pearlite of the steel plate for gas soft nitriding according to this embodiment.
[0052] (area ratio of retained austenite) Using the crystal orientation information obtained when measuring the area ratio of ferrite, the area ratio of the points determined to be fcc phase is taken as the area ratio of retained austenite. The sampling positions and observation positions of the observation samples are the same as those of the above-mentioned ferrite, the area ratio of retained austenite is obtained from each sample, and the average value of the area ratios of retained austenite of all the samples is taken as the area ratio of retained austenite of the steel plate for gas soft nitriding according to this embodiment.
[0053] (area ratio of bainite) In the steel plate for gas soft nitriding according to this embodiment, the portions other than ferrite, pearlite, retained austenite, and martensite are determined to be bainite. That is, the area ratio of bainite is calculated by subtracting the area ratios of ferrite, pearlite, retained austenite, and martensite from 100%.
[0054] (Average effective grain size) (Effective grain size difference) Using the crystal orientation information obtained when measuring the ferrite area ratio, a boundary where the orientation difference between adjacent measurement points is 15° or more is defined as a grain boundary from a figure determined to be a bcc phase on the inverse pole color map output by "OIM Analysis (registered trademark)", and the circle equivalent diameter of that grain is taken as the grain size of that grain. The grain size is used to calculate an average value for all grains in the observation field, and the effective grain size of that observation field is calculated. The sampling position and observation position of the observation sample are the same as those in the measurement of the ferrite area ratio described above, and the effective grain size is calculated from each sample, and the average value of the effective grain size of all samples is taken as the average effective grain size in the direction perpendicular to the rolling direction (sheet width direction) of the steel plate for gas soft nitriding according to this embodiment. Moreover, the difference between the largest and smallest effective grain size values at each observation position is taken as the effective grain size difference in the direction perpendicular to the rolling direction of the steel plate for gas soft nitriding according to this embodiment.
[0055] (mechanical properties) The steel plate for gas soft nitriding according to the present embodiment may have a tensile strength of 370 MPa or more and an elongation of 13.0% or more, as generally required mechanical properties, measured in accordance with JIS Z2241:2011 using a No. 5 test piece of JIS Z2241:2011. The tensile strength may be 400 MPa or more, 440 MPa or more, 480 MPa or more, 520 MPa or more, 580 MPa or more, or 620 MPa or more. There is no need to set an upper limit for the tensile strength, but the tensile strength may be 880 MPa or less, 800 MPa or less, 760 MPa, 720 MPa or less, or 680 MPa or less. The elongation may be 14.0% or more, 16.0% or more, 18.0% or more, or 20.0% or more. There is no need to set an upper limit for the elongation, but the elongation may be 32.0% or less, 28.0% or less, or 26.0% or less. Furthermore, R / t, which is the limit bending radius R normalized by the plate thickness t, may be 3.0 or less. In this case, when cold working (pressing, etc.) is performed before the gas soft nitriding treatment, cracks and the like can be prevented during the cold working. In addition, the steel plate for gas soft-nitriding in this embodiment is intended to be applied to parts that transmit power around the engine after gas soft-nitriding treatment, and the goal is to achieve a surface hardness of 500 Hv or more and an effective hardening depth of 0.300 mm or more, which is a depth that is 50 Hv or more harder than the parent phase, by the gas soft-nitriding treatment (gas soft-nitriding parts are obtained with a surface hardness of 500 Hv or more and an effective hardening depth of 0.300 mm or more, which is a depth that is 50 Hv or more harder than the parent phase).
[0056] The surface hardness after gas soft nitriding is determined by the following method. The surface hardness after gas soft nitriding is a value obtained by measuring the Vickers hardness at any cross section in the thickness direction of the steel plate after gas soft nitriding. The measurement position may be such that the center of the indentation is located within a range of 50 μm or less from the surface where the hardness change in the thickness direction is small. If it is close to the surface, material flow occurs near the surface during hardness measurement, resulting in measurement errors, so it is preferable that the center of the indentation is located at a position 35 μm or more from the surface in the thickness cross section of the steel plate. The Vickers hardness may be measured based on JIS Z 2244-1:2020. The load during hardness measurement is 200 gf (Hv0.2), and the average value of measurements at three points at the above-mentioned depth in the thickness direction is taken as the surface hardness after gas soft nitriding. The cross section for measuring Vickers hardness is an arbitrary cross section in the thickness direction of a gas soft-nitrided part, which is roughly ground to #80 to #1000 and then mirror-polished with a polishing solution containing dispersed diamond powder with a grain size of 1 to 3 μm.
[0057] The effective hardening depth after gas soft-nitriding is measured by measuring the Vickers hardness at 0.05 μm intervals from the surface layer in the depth direction of an arbitrary cross section in the plate thickness direction of the steel plate after gas soft-nitriding. Three points are measured at the same depth, and the average value is taken as the Vickers hardness at that depth. In the obtained Vickers hardness profile, when the plate thickness is t, the depth of the region that is 50 Hv higher than the average (average hardness) of the Vickers hardness measured at three points at a position t / 4 in the plate thickness direction from the surface is measured, and this is taken as the effective hardening depth. The measurement load for Vickers hardness is 50 gf (Hv0.05), and the load is set so that the interval between each measurement point is 5 times or more the indentation size, or the measurement position is shifted in the plate surface direction.
[0058] The above are the microstructural requirements for satisfying the basic properties of steel plate for gas soft nitriding and the method for measuring them.
[0059] The thickness and width of the steel plate for gas soft-nitriding according to this embodiment are not particularly limited, but in consideration of the expected application to parts, the thickness is preferably 1.2 to 3.6 mm and the width is preferably 900 to 1500 mm. The steel plate for gas soft-nitriding according to this embodiment may be a so-called steel plate with mill edges (including steel strips, also called mill-edge steel plate), or a steel plate from which the mill edge portion has been removed by cutting (including steel strips, also called cut-edge steel plate).
[0060] <Gas soft nitriding parts> The gas soft-nitriding part according to the present embodiment will be described. The gas soft-nitriding part according to the present embodiment can be obtained by processing the above-mentioned steel plate for gas soft-nitriding according to the present embodiment as necessary, and then performing a gas soft-nitriding treatment.
[0061] (chemical composition) The chemical composition of the gas soft-nitriding part according to this embodiment is the same as that of the steel plate for gas soft-nitriding according to this embodiment, which is the raw material, except for the nitrided region of the surface layer (for example, at a position tc / 4 in the thickness direction from the surface, where tc is the thickness of the part), and therefore a description thereof will be omitted.
[0062] (nitriding area) The gas soft-nitrided part according to this embodiment has a nitrided region on the surface of which nitrides are present. In the gas soft-nitrided part according to this embodiment, the surface hardness is 500 Hv or more, and the thickness (effective hardening depth) of the region in which the hardness is 50 Hv or more higher than the hardness of the parent phase (average hardness at the position tc / 4 in the thickness direction from the surface) is 0.300 mm or more. If the surface hardness is less than 500 Hv, or if the thickness of the region in which the hardness is 50 Hv or more higher than the hardness of the parent phase is less than 0.300 mm, a predetermined wear resistance cannot be obtained.
[0063] The surface hardness is determined by the following method as described above. The surface hardness of a gas soft-nitrided part is a value obtained by measuring the Vickers hardness at any cross section in the thickness direction of the gas soft-nitrided part. The measurement position may be such that the center of the indentation is located within a range of 50 μm or less from the surface where the hardness change in the thickness direction is small. If it is close to the surface, material flow occurs near the surface during hardness measurement, resulting in measurement errors, so it is preferable that the center of the indentation is located at a position 35 μm or more from the surface in the thickness cross section of the steel plate. The Vickers hardness may be measured based on JIS Z 2244-1:2020. The load during hardness measurement is 200 gf (Hv0.2), and the average value of measurements taken at three points at the above-mentioned depth in the thickness direction is taken as the surface hardness of the gas soft-nitrided part. The cross section for measuring the Vickers hardness is a surface that is roughly polished to #80 to #1000 and then mirror-polished with a polishing solution in which diamond powder with a grain size of 1 to 3 μm is dispersed on any cross section in the thickness direction of the gas soft-nitrided part.
[0064] The thickness of the region having a hardness 50 Hv or more higher than the hardness of the parent phase can be determined by the following method.
[0065] (The thickness of the region where the hardness is 50Hv or more higher than the parent phase) The Vickers hardness is measured at 0.05 μm intervals from the surface in the depth direction in any thickness direction cross section of the gas soft-nitrided part. Here, three points are measured at the same depth, and the average value is taken as the Vickers hardness at that depth. In the obtained Vickers hardness profile, when the thickness is tc, the depth of the region that is 50 Hv higher than the average (average hardness) of the Vickers hardness measured at three points at tc / 4 in the thickness direction from the surface is measured, and this is taken as the thickness of the region that is 50 Hv higher than the hardness of the parent phase. The load for measuring the Vickers hardness is 50 gf (Hv0.05), and the load is set so that the interval between each measurement point is 5 times or more the size of the indentation, or the measurement position is shifted in the direction of the plate surface.
[0066] (Metal structure) The metal structure of the gas soft-nitriding part in this embodiment is not limited, but may be the same as the raw material steel plate for gas soft-nitriding in this embodiment, except for the nitrided region of the surface layer (for example, at a position tc / 4 in the thickness direction from the surface).
[0067] <Manufacturing method> Next, a method for producing a steel plate for gas soft nitriding according to this embodiment will be described. The steel plate for gas soft nitriding according to this embodiment is obtained by a manufacturing method including the following steps: If necessary, after the following steps (I) to (IV), a pickling step (V) or a skin pass step (VI) described later may be applied. (I) A heating step for heating a slab having a predetermined chemical composition. (II) The hot rolling process in which the slab after the heating process is subjected to rough rolling and finish rolling to produce hot-rolled steel sheets. (III) Cooling process for cooling the hot-rolled steel sheet after the hot rolling process (IV) Winding process for winding hot-rolled steel sheets after the cooling process Preferred conditions for each step will be described below. For conditions not described, known conditions can be applied.
[0068] (Heating process) In the heating step, a slab (e.g., a slab with a thickness of about 50 to 300 mm) manufactured by continuous casting and having the same chemical composition as the steel plate for gas soft nitriding according to the present embodiment described above is heated under the following conditions. By controlling the furnace temperature, the variation in the structure (grain size) in the plate width direction is reduced. This is presumably because the variation in the austenite grain size in the slab is reduced by controlling the furnace temperature. (a) Primary heating is performed by placing the material in a primary heating furnace whose atmospheric temperature is adjusted to 400 to 1260°C for 10 to 100 minutes. (b) performing secondary heating by placing the slab after the primary heating in a secondary heating furnace for 20 to 170 minutes, the atmosphere temperature of which is adjusted to a temperature higher than that of the primary heating and in a range of 950 to 1325°C; (c) The slab after the second heating is placed in a tertiary heating furnace whose atmospheric temperature is adjusted to 1130 to 1310° C. for 20 to 150 minutes, thereby carrying out tertiary heating. If any of the conditions of the above primary heating to tertiary heating are outside the range, the effective grain size difference in the sheet width direction exceeds 10.0 μm. The atmospheric temperature during this slab heating refers to the temperature inside the furnace controlled by a thermometer installed in the furnace. This heating method is necessary even if the slab is not cooled to room temperature, and the temperature of the slab charged into the primary heating furnace is preferably 800°C or less, more preferably 100°C or less.
[0069] (Hot rolling process) In the hot rolling process, the heated slab is subjected to rough rolling and finish rolling to form a hot-rolled steel sheet. In the rough rolling, the cumulative reduction is set to 60% or more and 90% or less. The cumulative reduction is the thickness reduction rate calculated using the slab thickness t0 and the thickness after rough rolling t1. If the cumulative reduction rate in rough rolling is less than 60%, the average effective grain size in the width direction will not be 35.0 μm or less. If the cumulative reduction rate exceeds 90%, the average effective grain size will be less than 8.0 μm. The temperature for the rough rolling may be in the range of 1000 to 1200° C., and the number of times of rolling may be set based on the load on the rolling mill. The number of times of rolling in the rough rolling is preferably 5 times, for example. In the finish rolling, the rolling start temperature is set to 980°C or higher, the rolling reduction in the final pass is set to 4 to 30%, and the finish temperature is set to 840 to 960°C. When the finish rolling start temperature is less than 980°C, the difference in effective grain size in the width direction of the steel plate exceeds 10.0 µm. Furthermore, if the reduction rate in the final pass is less than 4%, the rolling strain becomes non-uniform, causing the effective grain size difference in the width direction of the steel sheet to exceed 10 μm. On the other hand, if the reduction rate in the final pass is more than 30%, grain growth causes the average effective grain size in the width direction to exceed 35.0 μm. Furthermore, when the finishing temperature is less than 840° C., the average effective grain size in the width direction is less than 8.0 μm, whereas when the finishing temperature exceeds 960° C., the average effective grain size in the width direction exceeds 35.0 μm. In addition, as long as the reduction rate in the final pass is within the above range, the number of passes of rolling is not particularly limited, and may be set based on the load on the rolling mill. The number of passes of the finish rolling is preferably, for example, 5 passes. In the hot rolling step and the subsequent cooling and winding steps, the temperature is preferably controlled based on the surface temperature at the center in the width direction.
[0070] (cooling process) (winding process) After the finish rolling is completed (after the final pass is completed), water cooling is started within 2.0 seconds, and water cooling is completed within 20.0 seconds after the start of cooling. The strip is then coiled at 430 to 580°C. If the time from the reduction in the final pass to the start of cooling exceeds 2.0 seconds, the area ratio of ferrite will be less than 30.0%. The cooling start time is not limited as long as it is within 2.0 seconds after the completion of finish rolling, but may be 0.4 seconds or more, or may be 0.6 seconds or more, taking into consideration the air-cooling zone distance in temperature measurement after rolling, etc. Furthermore, if the water cooling time to the coiling temperature range of 430 to 580°C after the start of cooling exceeds 20.0 seconds, the area ratio of ferrite is less than 30.0% and the area ratio of bainite exceeds 70.0%. If the coiling temperature is less than 430°C, the area ratio of martensite exceeds 5.0%. On the other hand, if the coiling temperature exceeds 580°C, the effective grain size difference in the width direction of the steel sheet exceeds 10.0 μm.
[0071] (pickling process) (Skin pass rolling process) After the coiling process, pickling may be performed. Pickling is intended to remove scale from the steel sheet surface, and may be performed by a known method. In addition, the steel sheet after pickling may be subjected to skin pass rolling. Skin pass rolling can not only suppress the yield point elongation by introducing mobile dislocations, but also increase the dislocation density on the steel sheet surface. When performing skin pass rolling, conditions may be set so that the elongation is not significantly reduced. For example, the rolling reduction in skin pass rolling is preferably 0.5 to 5.0%. If the rolling reduction is less than 0.5%, the yield point elongation may not be suppressed, and if it exceeds 5.0%, dislocations may be introduced to the center in the sheet thickness direction, resulting in a reduction in ductility. EXAMPLES
[0072] Cast pieces having the chemical composition shown in Table 1 (units are mass%, the remainder being Fe and impurities) were used and heated, rolled, cooled and coiled under the conditions shown in Table 2 to produce coils with thicknesses of 1.2 to 2.3 mm and widths of 1000 to 1500 mm. In Table 1, the column for Equation 1 shows the calculated value of the left side of equation (1), and the column for Equation 2 shows the calculated value of the right side of equation (2).
[0073] [Table 1]
[0074] [Table 2]
[0075] A JIS No. 5 test piece was taken from the obtained steel sheet coil at a position 10 m from the tip of the longitudinal direction and at a position w / 2 in the width direction from the end in the width direction, and a tensile test was carried out at a tensile speed of 10 mm / min in accordance with JIS Z2241:2011 to measure the tensile strength (TS) and elongation (El). In addition, a bending test was carried out using a No. 3 test piece according to the method specified in JIS Z 2248: 2006, 6.1, Press Bending Method, and R / t, which is the limit bending radius R normalized by the plate thickness t, was measured. At that time, the bending radius was tested in increments of 0.5 times the plate thickness to determine the minimum R / t. In addition, the characteristics of the metal structure (area ratio, average effective grain size, and effective grain size difference) were measured using the method described above at seven locations: a depth of t / 4 from the surface and w / 8, w / 4, 3w / 8, w / 2, 5w / 8, 3w / 4, and 7w / 8 in the width direction from the end in the width direction. The results are shown in Table 3.
[0076] [Table 3]
[0077] Furthermore, ring test pieces as shown in Fig. 1 were taken from the obtained steel plate coil by shear trimming (punching using a trim die) centered on the 1 / 2, 1 / 4, and 1 / 8 positions in the width direction of the steel plate, and gas soft-nitriding treatment was carried out in an atmosphere of a mixed gas with a volume ratio of 45% nitrogen, 50% ammonia, and 5% carbon dioxide. The treatment temperature was 570°C, and the soaking time was 1 hour, and gas soft-nitriding treatment was carried out, and the shape change was investigated. As described above, the outer diameter was measured before and after the treatment in the rolling direction, the direction perpendicular to the rolling direction, and the directions at 45° and 135° to the rolling direction. If the change in outer diameter was 1 mm or less in all cases, the product was deemed to have passed the test. If the change in outer diameter exceeded 1 mm in any one of the three positions, the product was deemed to have failed the test.
[0078] Additionally, a 15cm square test piece was taken from half the width of the steel plate and gas nitrocarburizing was performed under the same conditions as above. A pin-on-disk type flat plate abrasion test was conducted on the test piece after gas nitrocarburizing. The sliding speed of the friction test piece in the abrasion test was 1m / s, and an abrasion load was applied for 3 hours under conditions of a surface pressure of 1000MPa, room temperature, and no lubrication. Test pieces with a thickness reduction of 300μm or more after the test were deemed to have failed. However, in cases where the strength or formability of the raw material steel plate for gas soft nitriding did not satisfy the target values, or where the shape change due to gas soft nitriding was significant, the steel was not suitable for use as a gas soft nitriding part, and therefore abrasion tests were not performed. The results are shown in Table 4.
[0079] [Table 4]
[0080] As can be seen from Tables 1 to 4, in the test numbers S4 to S6, S13, S14, S16 to S19, and S43 to S47, which are examples of the invention, the steel plates for gas soft-nitriding had sufficient tensile strength, elongation, and bending properties, and the shape change due to the gas soft-nitriding treatment was small. In addition, in these steel plates (corresponding to gas soft-nitriding parts) after the gas soft-nitriding treatment, the surface hardness was 500Hv or more, and the effective hardening depth, which is the depth at which the hardness is 50Hv or more higher than the parent phase, was 0.300mm or more. As a result, the steel plates after the gas soft-nitriding treatment also had excellent wear resistance. On the other hand, in the steel sheets S1 to S3, S7 to S12, and S15, which had chemical compositions outside the range of the present invention, and S20 to S42, which were produced under unfavorable manufacturing conditions, the tensile strength, elongation, or bending properties of the steel sheets for gas soft-nitriding were insufficient, or the shape change due to the gas soft-nitriding treatment was large, or the wear resistance after the gas soft-nitriding treatment was low. [Industrial Applicability]
[0081] According to the present invention, it is possible to provide a steel plate for gas soft-nitriding that can reduce the amount of shape change when gas soft-nitriding is performed as a surface hardening treatment, on the premise that the steel plate has generally required tensile strength, elongation, and bending properties, and therefore has high industrial applicability.
Claims
1. The chemical composition, in mass%, is C: 0.02-0.10%, Si: 0.001 to 0.100%, Mn: 0.70-1.65%, P: 0.060% or less, S: 0.005% or less, sol. Al: 0.020 to 0.450%, Ti: 0.020 to 0.120%, Cr: 0.100-0.450%, N: 0.0003 to 0.0070%, Cu: 0 to 0.40%, Ni: 0 to 0.30%, Nb: 0 to 0.080%, V: 0 to 0.080%, Mo: 0 to 0.100%, B: 0 to 0.0020%, Ca: 0-0.0100%, REM: 0-0.0100%, Sn: 0-0.0300%, Sb: 0 to 0.0100%, As: 0 to 0.0100%, Mg: 0 to 0.0300%, and The balance is Fe and impurities. The following formulas (1) and (2) are satisfied: The metal structure is, in area percent, Ferrite: 30.0 to 100.0%, Martensite: 0 to 5.0%, Bainite: 0 to 70.0% Retained austenite: 0 to 3.0% Perlite: 0-3.0%, It consists of: When the plate thickness is t and the plate width, which is the width in the direction perpendicular to the rolling direction, is w, and the effective crystal grain size is measured at a depth position of t / 4 from the surface and at seven positions of w / 8, w / 4, 3w / 8, w / 2, 5w / 8, 3w / 4, and 7w / 8 in the width direction from the end in the width direction, an average effective crystal grain size, which is an average of the effective crystal grain sizes at the seven points, of 8.0 to 35.0 μm; an effective crystal grain size difference, which is the difference between the maximum value and the minimum value among the seven effective crystal grain sizes, is 10.0 μm or less; Steel plate for gas nitrocarburizing. [sol. Al]+[Cr]≦0.482...Formula (1) 94 < 64×[Mn] + 156×[Cr] + 190×[sol.Al] - 9×[Mn] 2 - 86×[Cr] 2 - 328×[sol.Al] 2 ··· Equation (2) Here, the [element symbol] indicates the content in mass % of the element represented by the element symbol.
2. The chemical composition, in mass%, Cu: 0.01-0.40%, Ni: 0.01 to 0.30%, Nb: 0.001-0.080%, V: 0.001-0.080%, Mo: 0.001-0.100%, B: 0.0001 to 0.0020%, Ca: 0.0001-0.0100%, REM: 0.0001-0.0100%, Sn: 0.0001 to 0.0300%, Sb: 0.0001 to 0.0100%, As: 0.0001 to 0.0100%, Mg: 0.0001-0.0300%, Contains one or more selected from the group consisting of: The steel plate for gas soft nitriding according to claim 1.
3. The tensile strength of the No. 5 test piece of JIS Z2241:2011 is 370 MPa or more and the elongation is 13.0% or more. The steel plate for gas soft nitriding according to claim 1 or 2.
Citation Information
Patent Citations
Production of nitriding steel sheet excellent in formability
JP1997025513A
Steel for soft-nitriding, excellent in cold forgeability and pitting resistance
JP1998306343A
Steel sheet for nitrocarburizing treatment and manufacturing method therefor
JP2009068057A
Manufacturing method for cold-rolled steel sheets for nitriding treatment
JP4462264B2
Hot-rolled steel for gaseous nitrocarburizing and manufacturing method thereof
WO2012141297A1